Aspects of the epidemiology of Theileria parva infections in cattle and African buffalo (Syncerus caffer) in South Africa revealed by tick transmission and sub-inoculation of blood - Penzhorn, Barend Louis (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2011.